THE ACTIVITIES OF IMAM ABU HANIFA ON THE SCIENCE OF HADIS - Mirzaakhmedov Karimullo (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the following article the introduction of the Imam Abu Hanifa into the science of Abu Hanifa, his period of being disciple to the Imam Hammad and other scholars and his hadis studies, his being educated from Ata ibn Abu Raba and other tabiins are studied based on the comparative data retrieved from the diverse sources. Abu Hanifa began to focus on issues of jurisprudence (Islamic jurisprudence) and began to teach this science to others.